DIFICULDADES RELACIONADAS AO USO DE MEDICAMENTOS POR IDOSOS: UM RELATO DE CASO - Pieper, Mariane; Holzle, Daiana E. d. M.; Bandeira, Vanessa A. C.; Oliveira, Karla R. d. (Salão do Conhecimento, 2013)
Resumo